2009
DOI: 10.1007/s11055-009-9205-8
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Cognitive Functions in Children with Epilepsy

Abstract: The aim of the present work was to study the causes and structure of interictal cognitive and emotionalpersonality impairments in children with different types of epilepsy. A total of 40 children were studied, aged from eight to 18 years. Symptomatic epilepsy was diagnosed in 31 patients (77.5%) and idiopathic epilepsy in nine (22.5%). Cognitive functions were compared in relation to the type of epilepsy, type of seizures, and treatment with antiepileptic and its efficacy. The results showed that intellectual-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 2 publications
0
6
0
2
Order By: Relevance
“…For example, Sharma et al [11] concluded that gender had no impact on neurological and psychological deficits among epileptic children. Other comparable results, such as Hoare and Kerley [29], found gender difference to be inconsistent as a predictor of psychological problems in children with epilepsy. Studies that found sex to predict cognitive functions have shown that male epileptic children had more neurological deficits than their female counterparts, but female epileptic children had higher mean psychological deficits.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…For example, Sharma et al [11] concluded that gender had no impact on neurological and psychological deficits among epileptic children. Other comparable results, such as Hoare and Kerley [29], found gender difference to be inconsistent as a predictor of psychological problems in children with epilepsy. Studies that found sex to predict cognitive functions have shown that male epileptic children had more neurological deficits than their female counterparts, but female epileptic children had higher mean psychological deficits.…”
Section: Discussionmentioning
confidence: 77%
“…Other similar results show that gender is inconsistent as a predictor of psychological problems in children with epilepsy. Hoare and Kerley [29] found no gender difference but Austin et al [30] found that boys had more problems than girls, whereas a previous study of children with chronic epilepsy by Austin et al showed that girls with more severe seizures had the most difficulties.…”
mentioning
confidence: 98%
“…Seu tratamento correto envolve muitas questões além do controle das crises, incluindo aspectos cognitivos e sociais 2 . É bastante comum que crianças com epilepsia tenham dificuldades de aprendizagem e déficits cognitivos 3 . Os problemas cognitivos dos pacientes com epilepsia são multifatoriais, incluindo fatores clínicos e demográficos, como: idade de início, frequência das crises, tipo de crise, causa da epilepsia, drogas antiepilépticas e duração da epilepsia 4 .…”
Section: Funcionamento Intelectual Em Pacientes Pediátricos Com Epileunclassified
“…Epilepsy is a common pediatric problem, and of considerable challenge to pediatricians [1,2]. Epilepsy can severely affect the development and function of immature brain, which may lead to cognitive or intellectual dysfunctions.…”
Section: Introductionmentioning
confidence: 99%